2013
DOI: 10.1007/s11357-013-9561-8
|View full text |Cite
|
Sign up to set email alerts
|

Age-related histological and zinc content changes in adult nonhyperplastic prostate glands

Abstract: To clarify age-related histological and Zn content changes in nonhyperplastic adult prostate glands, a quantitative morphometric and energy-dispersive X-ray fluorescence analyses were performed. The prostates were obtained from autopsies of 63 subjects aged 21-70 years who died mainly from trauma. It was found that histologically normal prostate tissue undergoes substantial changes throughout aging. These changes are reflected in an increase of the percent volume of the glandular lumen for the third to fifth d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 76 publications
(103 reference statements)
5
22
0
Order By: Relevance
“…In many Western industrialized countries, including North America, PCa is the most frequently diagnosed form of noncutaneous malignancy in males and, except for lung cancer, is the leading cause of death from cancer [4][5][6][7][8][9]. Although the etiology of BPH and PCa is unknown, some electrolytes and trace elements have been highlighted in the literature in relation to the development of these prostate diseases [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In many Western industrialized countries, including North America, PCa is the most frequently diagnosed form of noncutaneous malignancy in males and, except for lung cancer, is the leading cause of death from cancer [4][5][6][7][8][9]. Although the etiology of BPH and PCa is unknown, some electrolytes and trace elements have been highlighted in the literature in relation to the development of these prostate diseases [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion followed from the qualitative analysis of individual data sets [24,38,53,[65][66][67]. It was also found that the percent volumes of these histological structures depend from age and the individual uroflowmetric characteristics of the subject [68].…”
Section: Discussionmentioning
confidence: 82%
“…It was also found that the percent volumes of these histological structures depend from age and the individual uroflowmetric characteristics of the subject [68]. Moreover, the variations of the individual percent volumes of histological structures and uroflowmetric characteristics also increase with age [24,67,68].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In our previous studies we demonstrated that the glandular lumen and, therefore, the prostatic fluid is the main pool of Zn, Se, and Rb accumulation in the normal human prostate (V. Zaichick & S. Zaichick, 2014. It was concluded that Zn, Se, and Rb are involved in functional features of prostate tissue.…”
Section: Resultsmentioning
confidence: 96%